Ghost town : seven ghostly stories - Nixon, Joan Lowery (New York : Delacorte Press, 2000)
A collection of stories about eerie encounters in various ghost towns across the United States. Each story is accompanied by an afterword about the actual town on which the story is based.
Keywords: Ghost towns -- Juvenile fiction; Children's stories, American; Ghost towns -- Fiction; Ghosts -- Fiction; Short stories